2022
DOI: 10.1021/acs.jafc.2c04868
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Application Enhances the Accumulation of Flavones and Anthocyanins in Bread Wheat (Triticum aestivum L.) Grains

Abstract: Selenium (Se) biofortification in wheat reduces the risk of Se deficiency in humans. Se biofortification increases the concentration of Se and anthocyanins in wheat grains. However, it is unknown whether Se biofortification can enhance flavonoids other than anthocyanins and the mechanism underlying flavonoid accumulation in wheat grains. Here, foliar application of selenite solution in wheat was conducted 10 days after flowering. Metabolite profiling and transcriptome sequencing were performed in Se-treated gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…Anthocyanin content in plants is highly influenced by external and internal factors [38,61]. The increased accumulation of anthocyanins under exogenous Se application was also observed in other crops and vegetables, such as bread wheat [43,62], maize [63], radish sprouts [45], and sweet basil [46]. In this regard, varieties with high anthocyanin content generally have higher Se contents [43,44].…”
Section: Discussionmentioning
confidence: 91%
“…Anthocyanin content in plants is highly influenced by external and internal factors [38,61]. The increased accumulation of anthocyanins under exogenous Se application was also observed in other crops and vegetables, such as bread wheat [43,62], maize [63], radish sprouts [45], and sweet basil [46]. In this regard, varieties with high anthocyanin content generally have higher Se contents [43,44].…”
Section: Discussionmentioning
confidence: 91%
“…Selenium (Se) is an essential micronutrient for human and animal health, and Se deficiency is a worldwide problem. As a critical component of 25 selenoproteins, Se plays essential roles in multiple physiological processes such as immune response, antioxidant defense, reduced cardiovascular risk, and thyroid hormone metabolism. Se absorption becomes a health concern when it goes below the recommended daily amount (50–200 μg), particularly in Asian nations that rely heavily on grains. As a result, increasing the micronutrient content of staple cereal grains via agricultural methods to prevent micronutrient malnutrition of Se in people has become a focus of study. …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it has been reported that exogenous application of Se upregulates the activity of phenylalanine ammonium lyase (PAL), 4-Coumarate:CoA-ligase (4CL), and epigenetic cytosine DNA methylation; these enzymes play key roles in the regulation of SAR in plants . Zhang et al demonstrated that foliar application of 200 mg/L Na 2 SeO 3 significantly enhanced the flavonoid content in wheat tissues . However, the application of Na 2 SeO 3 has both food safety and environmental concerns, largely due to its rapid diffusion and relatively narrow safe concentration range .…”
mentioning
confidence: 99%
“…18 Zhang et al demonstrated that foliar application of 200 mg/L Na 2 SeO 3 significantly enhanced the flavonoid content in wheat tissues. 19 However, the application of Na 2 SeO 3 has both food safety and environmental concerns, largely due to its rapid diffusion and relatively narrow safe concentration range. 20 For example, Na 2 SeO 3 can induce protein malformation in plants when the concentration exceeds the optimal level, thereby disrupting photosynthesis and antioxidative system function.…”
mentioning
confidence: 99%